Outpatient psychotherapy in Germany: an evaluation of the structural reform - Kruse, Johannes; Kampling, Hanna; Bouami, Soufiane Filali; Grobe, Thomas G.; Hartmann, Mechthild; Jedamzik, Johanna; Marschall, Ursula; Szecsenyi, Joachim; Werner, Samuel; Wild, Beate; Zara, Sandra; Heuft, Gereon; et al. (Deutsches Ärzteblatt, 2024)
Background - A structural reform of the German psychotherapy guideline in 2017 was intended to facilitate access to outpatient guideline psychotherapy. In the present study, we evaluate the effects of this reform in particular for patients with a comorbidity of mental disorders and chronic physical conditions (cMP). - Methods - Pre-post analyses of the two primary endpoints “percentage of mentally ill persons who have made an initial contact with a psychotherapist” and “waiting time for guideline psychotherapy” were carried out employing population-based and weighted routine statutory health insurance data from the German BARMER. The secondary endpoints included evaluations from the patients’ perspective, based on a representative survey of patients in psychotherapy, and an overview of the health care situation based on data from the National Association of Statutory Health Insurance Physicians (Kassenärztliche Bundesvereinigung, KBV) (study registration number: DRKS00020344). - Results - From 2015 to 2018, the percentage of mentally ill persons who had made an initial contact with a psychotherapist rose moderately, from 3.7% (95% confidence interval, [3.6; 3.7]) to 3.9% [3.8; 3.9] among persons with cMP and from 7.3% [7.2; 7.4] to 7.6% [7.5; 7.7] among those with mental disorders but without any chronic physical condition (MnoP). The new structural elements were integrated into patient care. The interval of time between the initial contact and the beginning of guideline psychotherapy became longer in both groups, from a mean of 80.6 [79.4; 81.8] to 114.8 [113.4; 116.2] days among persons with complex disease and from 80.2 [79.2; 81.3] to 109.6 [108.4; 111.0] days among persons with non-complex disease; most patients considered the waiting time. Approximately 8% of the patients who sought psychotherapy reported that they had not obtained access to a psychotherapist. - Conclusion - Neither in general nor for patients with cMP did the introduction of the structural reform appreciably lower the access barriers to psychotherapy. Further steps are needed so that outpatient care can meet the needs of all patients and particularly those with cMP.